STYLISTYKA POWIEŚCI MICHAIŁA BUŁHAKOWA MISTRZ I MAŁGORZATA - Chudzińska-Parkosadze, Anna (Przegląd Rusycystyczny, 2020)
The article deals with the problem of the stylistic of the novel by Mikhail Bulgakov The Master and Margarita. Literary style of the novel is often referred to satire, parody and grotesque. Nonetheless, Bulgakov’s novel can not be called a comic one, since its ideological essence belongs to the category of tragedy, in which catharsis goes beyond the existential situation of individual characters and transforms into the transcendental sphere. The style of the novel takes on the triple model, which is subject to speech style of the characters and narrative. The first stylistic group in the article is called high-style (statements of Woland, Yeshua Ha-Nozri and Pontius Pilate), the second style of low (expressions represent by Moskov dwellers) and the third — middle style (statements of Margarita and Woland’s retinue). The latter category is the most sophisticated and includes all the other stylistic groups. It combines both of the previous style as the Margarita, Koroviev and cat Behemoth act as intermediaries between the two worlds (the higher world of the truth and the lower world of falsehood).